1994
DOI: 10.1038/bjc.1994.142
|View full text |Cite
|
Sign up to set email alerts
|

Allelic loss on distal chromosome 17p is associated with poor prognosis in a group of Brazilian breast cancer patients

Abstract: Summary We examined loss of heterozygosity (LOH) for two loci on chromosome 17p (D17S5 and TP53), and erbB-2 gene amplification, in primary breast cancers from 67 Brazilian patients. We identified two distinct regions of LOH on chromosome 17p, one spanning TP53 and the other a more telomeric region (D17S5). Based on a short-term follow-up, Kaplan-Meier analyses of patients' disease-free survival showed that patients with LOH for D17S5, but retaining heterozygosity for TP53, were at higher risk of recurrence (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…By these means we were able to identify a distal region in which the frequency of loss was close to 70%; the data collected, however, are at the present insufficient for accurate survival analysis. Although the correlation of 17p13.3 LOH with prognosis have been seen by others in breast cancer (Nagai et al, 1994) an association of this genetic alteration with OS has never been previously investigated. Our results provide evidence that 17p subtelomeric lesions in breast tumours can predict disease-specific survival and, therefore, are associated with a more malignant phenotype.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…By these means we were able to identify a distal region in which the frequency of loss was close to 70%; the data collected, however, are at the present insufficient for accurate survival analysis. Although the correlation of 17p13.3 LOH with prognosis have been seen by others in breast cancer (Nagai et al, 1994) an association of this genetic alteration with OS has never been previously investigated. Our results provide evidence that 17p subtelomeric lesions in breast tumours can predict disease-specific survival and, therefore, are associated with a more malignant phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…In breast carcinomas 17p13.3 loss of heterozygosity (LOH) is independent of TP53 point mutations and is associated with a high S phase index (Merlo et al, 1994). A previous report on a panel of primary tumours from stage I-IV breast cancer patients have shown than LOH of D17S5 is associated with disease-free survival (Nagai et al, 1994). The general hypothesis being tested in our study is that allele losses at a specific chromosome location, framed by a well-mapped set of markers, could be associated with the clinical course of breast cancer.…”
mentioning
confidence: 99%
“…It is important to note though that these studies analysed TP53 mutations or p53 protein expression, and not LOH at this locus. Although there are a few studies in which loss of TP53 has been investigated for prognostic significance (Andersen et al, 1992;Nagai et al, 1994;Lizard-Nacol et al, 1997), the small number of cases included in these studies makes it hazardous to draw any definitive conclusions. It is thus unclear whether the lack of association between LOH at the TP53 marker and poor survival noted in these and the present study is of any underlying biological significance, or if it merely reflects the limited number of observations assessed by the statistical tests.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular evidence sug gests that a variety of genetic alterations involving genes regulating cell growth and proliferation contribute to breast cancer development and progression [1], Mutations on chromosome 17 are among the most fre quent genetic events associated with breast cancer etioloMaria A. Nagaigy. Considerable molecular evidence has indicated that chromosome 17 harbors several candidate tumor suppres sor genes, including nm23 [2], the prohibitin gene [3], the BRCA1 gene [4,5], the TP53 gene and at least two other putative tumor suppressor genes not yet defined [6][7][8], Loss of heterozygosity (LOH) for loci on chromosome 17 has been reported in 40-60% of sporadic breast tumors [7,9,10] and is distributed in at least five distinct regions [6,[11][12][13][14][15]. Two of these regions are located on chromo some 17p, one spanning the TP53 locus and one in 17p 13.3, distal to TP53 [6,11], Three or four distinct de leted regions have been reported on chromosome 17q [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable molecular evidence has indicated that chromosome 17 harbors several candidate tumor suppres sor genes, including nm23 [2], the prohibitin gene [3], the BRCA1 gene [4,5], the TP53 gene and at least two other putative tumor suppressor genes not yet defined [6][7][8], Loss of heterozygosity (LOH) for loci on chromosome 17 has been reported in 40-60% of sporadic breast tumors [7,9,10] and is distributed in at least five distinct regions [6,[11][12][13][14][15]. Two of these regions are located on chromo some 17p, one spanning the TP53 locus and one in 17p 13.3, distal to TP53 [6,11], Three or four distinct de leted regions have been reported on chromosome 17q [13][14][15]. One of these regions spans the recently cloned BRCA1 gene [5], which confers disease susceptibility in about 45% of families with breast cancer alone and the majority of families with breast and ovarian cancer [4,16,17].…”
Section: Introductionmentioning
confidence: 99%